Design and fabrication of suspension system for racing car / Muhammad Haziq Azizi Noor Ikhsan - Azizi Noor Ikhsan, Muhammad Haziq (2024)
This study focuses on the aerodynamic analysis and design optimization of a spoiler and mounting bracket for a Formula Student race car. The problem is the need to improve the car's performance through the addition of spoilers and mounting brackets to support the spoiler. The objective of the project is to design and fabricate a spoiler and mounting brackets. Computational Fluid Dynamics (CFD) simulations testing is employed as methodologies to analyze the airflow, visualize flow patterns, calculate drag and lift forces, and validate the proposed design modifications. The expected result of the project is designing a functional spoiler and mounting brackets that address the budget and manufacturing limitations. A measurable improvement is expected despite the design’s simplicity. The outcomes of this project will contribute to the development of better-performing Formula Student race cars, providing valuable insights for future designs and competitions.